Infomedia for factors contributing to internet abuse in the workplace / Azhar Abdul Aziz … [et al.] - Abdul Aziz, Azhar; Mokhsin @ Misron, Mudiana; Md Sarif, Shamsuddin; Mohd Rosli, Roshaliza; Mohd Lokman, Anitawati (Research Innovation Business Unit, 2014)
Internet is indispensable in the current working environment; in fact it has become a standard office facility. Using the internet for personal use during working hour beyond the acceptable usage levels either using office computer or personal smart phones are still an account of internet abuse. Internet abuse may lead to productivity loss, security incidents, liability and network congestion which therefore are a serious concern for the employers. Since there is a lack of emphasis for research on this area, therefore the aims of this study are statistically prove existence of internet abuse and gain better understanding of the phenomenon. . The three objectives of the research are, (1) to investigate the employees’ internet abuse activities, (2) to investigate the relationship between demographic, personality and external factors with the intention to abuse the internet and (3) to recommend countermeasure to overcome internet abuse during working hours. This research adopted the modified TPB (Theory of Planned Behaviour) as the research model. The study was conducted by distributing questionnaires to employees in three small-medium sized organizations in ICT sector located in Kuala Lumpur and Selangor. Further to that, interviews conducted with higher management, HR, IT, and an employee to get more information on the subject. This study would give insight into factors contributing to internet abuse in the workplace and the internet abuse activities that the employees engaged in which can then be used to plan adequately and manage the issue. It could help employees to increase the awareness and possibility of change in behaviour with regards to internet abuse through sharing the result of this study by the employers in monthly bulletin or incorporating the countermeasure in office policy.